PERAN SATUAN POLISI PAMONG PRAJA DALAM PENATAAN PEDAGANG KAKI LIMA (PKL) DI PASAR TUAH SERUMPUN KECAMATAN TUALANG KABUPATEN SIAK TAHUN 2021 - Susmita Yulia Putri; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Looking at the authority given to the Civil Service Police Unit, it is undeniable that the existence of the Civil Service Police Unit is very important and strategic in the administration of regional government in accordance with its scope of duties, including the implementation of public order and public peace. The focus topic of this research is